A biobased aliphatic polyester derived from 10-hydroxydecanoic acid: Molecular weight dependence of physical properties. (February 2020) - Gao, Mengyun; Leng, Xuefei; Zhang, Wenwen; Wei, Zhiyong; Li, Yang
Abstract: Poly(10-hydroxydecanoate) (PHDA) is of interest as a new-type aliphatic polyester due to its bioresource and flexible mechanical property. A series of PHDAs with varied molecular weights ( M n from 27 kg/mol to 74 kg/mol) were prepared by optimized melt polycondensation of 10-hydroxydecanoic acid (HDA). Through DSC, WAXD, POM and tensile tests, the effects of molecular weight on the physical properties, including thermal properties, crystallization behavior, crystal morphology, rheological behavior and mechanical properties of PHDA were studied in detail. The results demonstrated that the physical properties of PHDA largely rely on the molecular weight. In particular, the brittle-ductile transition of PHDA occurred when the molecular weight increased up to 55 kg/mol. With the increase of molecular weight, the elongation at break was largely improved and finally exceeded 1400%. The ultimate tensile strength kept about 20 MPa. Hence, PHDA has a PE-like mechanical property. Our work highlights that PHDA is a polymer with excellent performance, which provides an alternative to durable petroleum resourced packaging materials. Graphical abstract: Image 1 Highlights: Poly(10-hydroxydecanoate) (PHDA) is of interest as a sustainable aliphatic polyester. The dependence of physical properties of PHDA on molecular weight was explored. PHDA shows well flexible mechanical property like PE. PHDA is a promising alternative of durable petroleum resourced packaging materials.